Decomposition of the CO stretching vibration band of laboratory H2O–CO ices irradiated by heavy ions. Issue 3 (2nd October 2021) - Seperuelo Duarte, E; de Barros, A L F; da Silveira, E F; Domaracka, A; Boduch, P; Rothard, H
ABSTRACT: H2 O and CO molecules are the main constituents of the interstellar dust grain ice mantles. Infrared spectra of the ices in line of sights of young stellar objects and background stars have shown that the CO stretching vibration band can be decomposed into three main components: 2143, 2139, and 2136 cm −1, assigned to CO in different environment sites. The relative strengths between the components have been associated with an evolutionary track of the interstellar molecular clouds. H2 O:CO (3:2) and (10:1) ice samples were irradiated by 0.79 MeV/u 58 Ni 13+ ions to simulate the effects produced by heavy ion cosmic rays in typical interstellar ice mixtures. The CO stretching vibration band is decomposed into six Gaussian functions (2150, 2144, 2141, 2138, 2136, and 2133 cm −1 ) and their integrated absorbances were measured as a function of fluence. The results show that, at the final fluence, the component 2138 cm −1 is the main component of the CO stretching vibration band. The component 2150 cm −1 disappears at the beginning of irradiation. Based on the present and previous results, a time-scale for the components in the interstellar ices is proposed. For H2 O:CO ices in the interstellar medium, it is predicted that, after 1 Ma, the main components of the CO stretching vibration band are the 2138 and 2141 cm −1, due to the CO monomers and dimers, respectively.